Static conductance of nitrile-substituted oligophenylene and oligo(phenylene ethynylene) self-assembled monolayers studied by the mercury-drop method - Querebillo, Christine Joy Uy; Terfort, Andreas; Allara, David L.; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2013)
Static charge transport (CT) properties of nitrile-substituted oligophenylenes and oligo(phenylene ethynylene)s (NC-OPh and NC-OPE, respectively) assembled via the thiolate anchor on gold substrates were measured by the mercury drop junction technique. The derived attenuation factors (β), viz. 0.53 ± 0.1 and 0.30 ± 0.08 Å-1 for the NC-OPh and NC-OPE monolayers, respectively, correlate well with the literature values for the analogous nonsubstituted systems, suggesting that the attachment of the nitrile group to the OPh or OPE backbone does not significantly affect their transport properties. This finding provides a basis for the use of the nitrile moiety as a resonantly addressable group and as specific charge injection site in the measurements of dynamic CT by resonant Auger electron spectroscopy. The comparison between the static and dynamic β values for the NC-OPh monolayers implies that the static value corresponds to nonresonant injection conditions. This suggests, potentially, that the static CT can be performed more efficiently by controlling the specific molecular orbitals into which charge carriers are injected.
Gesehen am 10.12.2021